Modulating the Inflammatory Response to Wounds and Cancer Through Infection - López-Cuevas, Paco; Cross, Stephen J.; Martin, Paul (Frontiers in Cell and Developmental Biology, 2021)
The zebrafish (Danio rerio) has recently emerged as an excellent model to study cancer biology and the tumour microenvironment, including the early inflammatory response to both wounding and early cancer growth. Here, we use high-resolution confocal imaging of translucent zebrafish larvae, with novel automated tracking and cell:cell interaction software, to investigate how innate immune cells behave and interact with repairing wounds and early cancer (pre-neoplastic) cells expressing a mutant active human oncogene (HRASG12V). We show that bacterial infections, delivered either systemically or locally, induce a change in the number and behaviour of neutrophils and macrophages recruited to acute wounds and to pre-neoplastic cells, and that infection can modify cellular interactions in ways that lead to a significant delay in wound healing and a reduction in the number of pre-neoplastic cells. Besides offering insights as to how Coley’s toxins and other cancer bacteriotherapies may function to reduce cancer burden, our study also highlights novel software tools that can be easily adapted to investigate cellular behaviours and interactions in other zebrafish models.